ANALISIS KREDIT MACET PADA KREDIT USAHA RAKYAT (KUR) PT BANK RAKYAT INDONESIA CABANG SAMARINDA 1 UNIT CITRA NIAGA - Sari, Septia Epria (EKONOMIA, 2019)
Analysis of Bad Debt in Kredit Usaha Rakyat (KUR) PT Bank Rakyat Indonesia Branch Samarinda 1 Unit Citra Niaga. This study aims to find out and analyze bad debts on the credit of kreditusaha rakyat (KUR) of PT Bank Rakyat Indonesia Samarinda Branch 1 Unit Citra Niaga in 2016 and 2017, and compare bad debts in kredit usaha rakyat (KUR) PT Bank Rakyat Indonesia Samarinda Branch 1 Unit Citra Niaga in 2017 by 2016. Theoretical basis in this study is financial accounting is a process that ends on the preparation of financial statements that concern the company as a whole to be used by both internal parties and external parties.Collection in this research using field research and literature research. The analysis tool used for this research is the ratio of Non Performing Loan (NPL). The results of this study indicate that bad loans in the kredit usaha rakyat (KUR) PT Bank Rakyat Indonesia Branch Samarinda 1 Unit Citra Niaga in 2016 amounting to Rp. 49.654.145,00 or sebsar 0.86% and in 2017 the bad credit ofÂ Rp. 69.240.714 or at 1.26%. The increase in non-performing loans is Rp. 19,586,569.00 or 0.40% from 2016. Hence the hypothesis is acceptable, although an increase of 0.40% from 2016, as it does not exceed PT Bank Rakyat Indonesia's Non Performing Loan (NPL) of 5%. The conclusion of this research is that there is an increase of bad debts on people business credit (KUR) of PT Bank Rakyat Indonesia Branch of Samarinda 1 Unit Citra Niaga which is Rp. 19,586,569.00 or by 0.40% from 2016.